The The Evidence for a Role of Bacteria and Viruses in Cardiovascular Disease - Pierce, Grant N; Deniset, Justin F; Resch, Craig T; Mourin, Muntahi; Dibrov, Elena; Dibrov, Pavel (Scripta Medica, 2022)
Inflammation plays a critical role in atherosclerosis and cardiovascular disease. Bacteria and viruses are major causative agents of inflammation in the body which normally develops as a response to infection. It is a logical extention, therefore, to believe bacterial and viral infections may be involved in a variety of presentations of cardiovascular diseases. The purpose of this review is to describe the data and conclusions to date on the involvement of these infectious agents in the induction of cardiovascular disease. The review also discusses the various specific bacteria and viruses that have been implicated in cardiovascular disease and the mechanisms, if known, that these agents induce cardiovascular disease.